Quantitative Estimation of Annual Soil Loss by Integration of Remote Sensing, GIS, and Universal Soil Loss Equation (Case Study: Tartus District, Syria) - Al-Abed, Mohammad; Salhab, Jalal; Ebrahim, Hani; Dweri, Safa (Annals of Arid Zone, 2019)
This paper describes the procedures employed to integrate Remote Sensing(RS) and Geographic Information System (GIS) techniques in an effort to characterize thespatial distribution of the risk of soil erosion by water on lands of Tartus district, Syria.The universal soil loss equation (USLE) is used to calculate the annual soil loss rates forTartus soils. Mainly Landsat Enhanced Thematic Mapper (ETM) dated 5/2009, thematicmaps such as land capabilities, landuse, digital elevation model (DEM) and climate datawere used to determine USLE factors. Integration of these data sets resulted in a mapof polygons with unique combinations of USLE factor values. The study showed thatwater erosion mainly threatens those soils on hilly lands where vegetation is sparse orabsent and exposed to heavy rainfall. Mostly these lands extend around these townsand villages of Tiro, Jwibat, Hrison, Shiekh Bader, HamamWasel, Dulbeh and Safasif,where these soil loss was about 150 t h-1 y-1 which account for 0.13% of the soil loss.These quantities of annual soil loss can be considered as a very severe amounts, andif this water erosion persists at these high rates, the soil will be eroded and the parentmaterial will be exposed in these regions. The study also mentioned a package ofremedial measures so as to combat land degradation in the study area.Key words: Water erosion, USLE, Landsat ETM, GIS, Sustainable land use, Tartus.